Experimental study on turning characteristics of KVLCC2 tanker in long-crested irregular waves. (15th January 2022) - Kim, Dong Jin; Choi, Hujae; Yun, Kunhang; Yeo, Dong Jin; Kim, Yeon Gyu
Abstract: In this paper, turning characteristics of KVLCC2 tanker in long-crested irregular waves are investigated by 1/100 scaled free-running model tests. Three kinds of model propulsion points are determined in calm water tests, which correspond to the full-scale calm water speeds of 4.0, 7.0, and 15.5 knots. Turning circle tests are performed in long-crested irregular head waves of sea state 5 and 6, with variations of the model propulsion points. In order to obtain the statistical data on the manoeuvring behaviours of the model in irregular waves, irregular waves per each sea state are generated with five seeds, in other words, five kinds of superposition of regular waves. Initial and steady turning characteristics of the model ship are analyzed by using the indices proposed in the previous studies. The deviations of initial turn trajectories depending on sea state are relatively small, compared to the deviations of steady turn trajectories. Drifting distances of steady turns increase with increasing sea states, and they are remarkably increased with decreasing ship advance speeds. With the lowest model propulsion point corresponding to full-scale 4 knots, the model ship cannot turn in most runs under sea state 6 waves. Next, with the model propulsion point corresponding to full-scale speed of 7 knots, turning circle tests are performed in regular waves in order to compare the trajectory drifts in regular waves with those in irregular waves. Five kinds of regular waves are generated following the representative parameters of sea state 6 irregular waves such as significant, mean heights, modal, mean, and energy periods. Turning trajectories in regular waves are most similar to those in irregular waves in case that the regular waves have the mean height and the energy period of irregular waves. Finally, course-keeping and +35° initial turning tests with lowest propulsion point are carried out in sea state 6 long-crested irregular waves, in order to investigate low speed course-keeping and turning abilities depending on the wave incident angles. Wave incident angles are varied from 30° to 330° at intervals of 30°. In port beam and port stern quartering waves, the steering moments by rudder cannot overcome the wave drifting forces and moments, so the model ship has problems on course-keeping and turning manoeuvres. Highlights: Free-running turning circle tests for a KVLCC2 model were performed in long-crested irregular waves. Initial and steady turning characteristics of the model in irregular waves are statistically analyzed. Equivalent regular waves which show similar turn trajectories to those in irregular waves are searched. Low speed course-keeping and turning tests were carried out depending on the incident angles of long-crested irregular waves, manoeuvring problems were investigated in the specific regions.